The potential of yeasts from the oil-contaminated soil and mangrove rhizosphere for degrading crude oil - NUR HIDAYATUL ALAMI; LUTHFI LAILATUL MAULIDIYA; N D KUSWYTASARI; ENNY ZULAIKA; MAYA SHOVITRI (Society for Indonesian Biodiversity, 2019)
Abstract. Alami NH, Maulidiya LL, Kuswytasari ND, Zulaika E, Shovitri M. 2019. The potential of yeasts from the oil-contaminated soil and mangrove rhizosphere for degrading crude oil. Biodiversitas 20: 1833-1838. Bioremediation of crude oil contaminated soil eventually depends on the activities of microorganisms to degrade contaminants. Bioaugmentation, through the addition of microbial culture to contaminated soil, can be used to enhance degradation rates. This research aimed to determine the effect of yeast formulations isolated from the oil-contaminated soil and mangrove rhizosphere to degrade crude oil and evaluate the most effective yeast formulation and incubation timefor crude oil degradation. This research was conducted by subculturing yeast in the slant agar medium, screening hydrocarbonoclastic yeast in crude oil- Bushnell Hass Mineral Salt (BHMS) medium, biodegradation test, measuring the total cell number with Total Plate Count (TPC), Total Petroleum Hydrocarbon (TPH) test with the gravimetric method, and measuring soil moisture content. The design of the research was Completely Randomized Factorial Design with 3 replications. Data were analyzed quantitatively by using statistical tests for TPC and TPH, while a descriptive qualitative test analyzed soil moisture. The result showed that yeast formulation and incubation time affected crude oil degradation. An effective yeast consortium for oil degradation is T20 consortium with an incubation period of 30 days, which result in 72.26 % oil degradation.